Targeting Beta-Amyloid at the CSF: A New Therapeutic Strategy in Alzheimer’s Disease - Menendez-Gonzalez, Manuel; Padilla-Zambrano, Huber S.; Alvarez, Gabriel; Capetillo-Zarate, Estibaliz; Tomas-Zapico, Cristina; Costa, Agustin (Frontiers in Aging Neuroscience, 2018)
Although immunotherapies against the amyloid-β (Aβ) peptide tried so date failed to prove sufficient clinical benefit, Aβ still remains the main target in Alzheimer’s disease (AD). This article aims to show the rationale of a new therapeutic strategy: clearing Aβ from the CSF continuously (the “CSF-sink” therapeutic strategy). First, we describe the physiologic mechanisms of Aβ clearance and the resulting AD pathology when these mechanisms are altered. Then, we review the experiences with peripheral Aβ-immunotherapy and discuss the related hypothesis of the mechanism of action of “peripheral sink.” We also present Aβ-immunotherapies acting on the CNS directly. Finally, we introduce alternative methods of removing Aβ including the “CSF-sink” therapeutic strategy. As soluble peptides are in constant equilibrium between the ISF and the CSF, altering the levels of Aβ oligomers in the CSF would also alter the levels of such proteins in the brain parenchyma. We conclude that interventions based in a “CSF-sink” of Aβ will probably produce a steady clearance of Aβ in the ISF and therefore it may represent a new therapeutic strategy in AD.